The Right of Public Employees to Run for Parliament in Iraqi Legislation: A Comparative Study - Salim, Salim; Mohamed, Manal (Journal of Legal Sciences, 2026)
Political rights are among the most important rights enjoyed by a human being, as a person's political participation contributes to shaping his present and determining his future. Among these rights is the right of a public employee to nominate himself for membership in the House of Representatives - parliament - as it is the true mirror that reflects the extent of progress achieved in the field of democracy. Therefore, most international covenants and instruments stipulate this right, and constitutions have been keen to establish this right within the general principle of political rights. Legal legislation has regulated this right and set general controls and restrictions for it. Countries’ legislation has varied in its strictness or leniency, depending on the nature and philosophy of the political system in place in the country, and the role of the judiciary in monitoring this right.Hence, our research, which we divided into three sections, the first entitled (the nature of the public employee’s right to nominate), the second entitled (the legal basis for the right to nominate), and the third entitled (the general controls for nomination and the special restrictions that apply to it, and the role of the judiciary in monitoring it).then we reached the conclusion of the research, which contained the most important results, including that the nature of candidacy is considered synonymous with the term freedom, the Iraqi legislator’s strictness in some general controls for candidacy, the absence of a constitutional and legal organization of the political rights of the public employee in Iraq, and the issuance of a set of recommendations, the most prominent of which is the necessity of organizing the political rights of the public employee constitutionally and legally, and easing some general controls for candidacy, and demanding that this be amended.